PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK MODEL STUDENT FACILITATOR AND EXPLAINING TERKAIT KEMAMPUAN KOMUNIKASI MATEMATIS DAN MINAT BELAJAR - Apriliani, Apriliani; Sujiarto, Heru (Uninus Journal of Mathematics Education and Science (UJMES), 2023)
This research is motivated by the absence of teaching tools that suit the needs of students and the low ability of mathematical communication and interest in learning. This is the main reason for the need to develop student facilitator model worksheets and explain mathematical communication skills and interest in learning. This study aims to determine the feasibility, ability test results, and interest in learning from the developed student worksheets. This research method is Research and Development with the ADDIE design. The data sources in this study were expert validators and class X IPS 1 students. The data collection instruments used were expert validation sheets, ability test sheets, and learning interest questionnaire sheets. Data were analyzed using proportions written according to their qualifications. Based on the analysis that has been carried out, it can be interpreted that the developed student worksheets is feasible to use, the results of the test of mathematical communication skills show that students of class X IPS 1 have good abilities, and have an interest in learning mathematics. It is suggested that the developed student worksheets can be an alternative tool for learning mathematics, it is necessary to carry out further trials with a larger number of students so that the results are more varied and increase the number of validators so that the quality of the eligibility of student worksheets can be even better.